DPIRS as an integrated approach to asses natural resources status and development - Wahyu Widiyono (Indonesian Journal of Applied Environmental Studies, 2022)
Environmental problems included biotic, abiotic, and social problems, therefore, to overcome them, various scientific disciplines are needed as well as the characteristics of environmental science itself. As consequences of population growth, industrial development, and technological progress, environmental problems are more complex. Therefore, appropriate research methods are needed to overcome new problems that arise as a result of these developments. UNEP recommends a research method called the DPSIR (Driving force–Pressure–State–Impact–Response) model that can describe the interactions between various environmental and social factors. This method has been applied as an approach to analyzing environmental problems in many countries around the world, including Indonesia. The Ministry of Environment and Forestry (KLHK) and some researchers in Indonesia have also applied the DPSIR method to assess environmental status both nationally and regionally. So far, the DPSIR method is still quite well applied to analyze environmental problems, although some scientists highlight the need for this method to be supplemented with other models to improve results.